The Palgrave Handbook of Digital Russia Studies - Gritsenko, Daria; Wijermars, Mariëlle; Kopotev, Mikhail (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access handbook presents a multidisciplinary and multifaceted perspective on how the 'digital' is simultaneously changing Russia and the research methods scholars use to study Russia. It provides a critical update on how Russian society, politics, economy, and culture are reconfigured in the context of ubiquitous connectivity and accounts for the political and societal responses to digitalization. In addition, it answers practical and methodological questions in handling Russian data and a wide array of digital methods. The volume makes a timely intervention in our understanding of the changing field of Russian Studies and is an essential guide for scholars, advanced undergraduate and graduate students studying Russia today.